Comparative Photovoltaics of P3HT:N2200 and P3HT: Small-Gap Fullerene Ethyl-Nipecotate Bulk Heterojunction Structures - Uddin, Md. Nasir; Islam, Rafiqul; Rahman, Muhibur; Chawdhury, Nazia (Makara Journal of Science, 2022)
This work deals with the study on the optical absorption and photoluminescence spectra of a p-type organic semiconducting polymer, regioregular poly 3-hexylthiophene-2,5-diyl (P3HT) and the absorption spectra of an n-type fullerene-based small-gap fullerene-ethyl nipecotate (Fullerene-EN) and a non-fullerene-based polynaphthalene bithiophene (N2200) semiconducting materials. The band gap of P3HT, N2200, and small-gap fullerene-ethyl nipecotate are 2.42, 1.65, and 1.51 eV, respectively, calculated from experimental results through the Tauc equation. Active layers with blends of P3HT and small-gap fullerene-ethyl nipecotate and P3HT and N2200 have been used to fabricate bulk heterojunction (BHJ) structures. The P3HT:N2200 BHJ structure follows the current density versus voltage characteristics of a photovoltaic device with 0.28% power conversion efficiency, 1.58 mA/cm2 short-circuit current density, and 41% fill factor. However, the P3HT:small-gap fullerene-ethyl nipecotate structure does not show any photovoltaic J–V characteristics.